Silicon-on-Insulator Technology: Materials to VLSI - Colinge, Jean-Pierre (Springer US, 2004)
Silicon-on-Insulator Technology: Materials to VLSI, Third Edition, retraces the evolution of SOI materials, devices and circuits over a period of roughly twenty years. Twenty years of progress, research and development during which SOI material fabrication techniques have been born and abandoned, devices have been invented and forgotten, but, most importantly, twenty years during which SOI Technology has little by little proven it could outperform bulk silicon in every possible way. The turn of the century turned out to be a milestone for the semiconductor industry, as high-quality SOI wafers suddenly became available in large quantities. From then on, it took only a few years to witness the use of SOI technology in a wealth of applications ranging from audio amplifiers and wristwatches to 64-bit microprocessors. This book presents a complete and state-of-the-art review of SOI materials, devices and circuits. SOI fabrication and characterization techniques, SOI CMOS processing, and the physics of the SOI MOSFET receive an in-depth analysis